Investigation of Cu/TiO2 synthesis methods and conditions for CO2 photocatalytic reduction via conversion of bicarbonate/carbonate to formate. (April 2023) - Adamu, Abdullahi; Isaacs, Mark; Boodhoo, Kamelia; Abegão, Fernando Russo
Abstract: This work is aimed at improving the photocatalytic activity of TiO2 in the reduction of CO2 . TiO2 and Cu/TiO2 at 5 wt% copper bulk loading were synthesised using the sol-gel method at a pH of 0.4 and 1.5. The synthesised pure TiO2 samples, alongside the commercial TiO2 (Degussa® P25), were also doped with copper via the incipient wetness method. The low pH and the presence of copper inhibited the anatase-rutile transformation. Copper existed in Cu(I) and Cu(II) states in all the doped samples, with the Cu(I) to Cu(II) ratio intimately linked with the anatase to rutile ratio. The UPS data have shown the type II band offset between TiO2 and CuO. The performance of the samples prepared was tested through the reduction of sodium bicarbonate-carbonate buffered at pH > 8. Commercial TiO2 impregnated with Cu demonstrated the highest formate production rate of 173 µmol·g −1· h −1 at pH 11. This study demonstrated the synergetic effect of the anatase-rutile mixture of phases, the reaction pH, and the copper dopant in improving the photocatalytic activity of TiO2 . Graphical Abstract: ga1 Highlights: The photocatalytic activity of titania (TiO2 ) depends on its phase composition. Cu dopant improves light absorption of TiO2 and enhance charge carrier separation. The pH of the sol-gel method plays an important role in controlling TiO2 phase and Cu forms distribution. Different forms of Cu build an energy favourable staggered band offset at the interface with TiO2 . The photocatalytic CO2 reduction is influenced by change in the pH of the reaction medium.